Role Of Exchange Leader Members In Increasing Employee Performance Post Covid-19 - Indah rahayu; Ida Wahyuningsih (LPPM Universitas An Nuur, 2022)
Background: The Covid-19 Virus Disease has spread and spread to all regions in Indonesia. With the widespread spread of the Covid-19 virus having an impact on the quality of the human resources in a company, the human resources in a company play an important role in sustainability, a company in carrying out its duties. Leadership is an important element in a company, without leadership from a leader, a company will experience setbacks. Leadership is an important element in a company, without leadership from a leader, a company will experience setbacks. leader member exchange is an improvement in the relationship between leaders and employees who are able to improve performance between the two with the existence of a leader member exchange this has a positive impact on making employees more voluntary about their work and feel more comfortable when working with their leaders.Purpose: The purpose of this study is to improve employee performance besides leader member exchange, perceived organizational support (POS) and Job Satisfaction as moderating variablesMethods: The research method used is a quantitative methodResults: Results: The results of the study found constructs in employee performance efforts, namely perceived organizational support (POS) and job satisfactionConclusion: Leadership is an important element in a company, without leadership from a leader, a company will experience setbacks. Every leader basically has a different behavior in leading. Leadership carried out by a leader in influencing the behavior of others in accordance with the wishes that are influenced by the nature of the leader himselfSuggestion: For the future agenda we plan to validate the measurement of both concepts and test the proposed model with qualiitative methods